2021
DOI: 10.2807/1560-7917.es.2021.26.38.2100833
|View full text |Cite
|
Sign up to set email alerts
|

mRNA vaccine effectiveness against COVID-19-related hospitalisations and deaths in older adults: a cohort study based on data linkage of national health registries in Portugal, February to August 2021

Abstract: Through deterministic data linkage of health registries, mRNA vaccine effectiveness (VE) against COVID-19-related hospitalisations and deaths was measured in 1,880,351 older adults. VE against hospitalisations was 94% (95% confidence interval (CI): 88–97) and 82% (95% CI: 72–89) for those 65–79 and ≥ 80 years old, with no evidence of waning 98 days after dose two. VE against mortality was 96% (95% CI: 92–98) and 81% (95% CI: 74–87) in these two age groups.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 6 publications
6
61
0
Order By: Relevance
“…After completed vaccination schemes, we observed a decay of the VE estimates with time, particularly against symptomatic infection and in the 80 and more yo cohort, where VE decay was observed for both symptomatic infection and hospitalizations. The drop over time of VE against symptomatic infection has also been reported by several authors [14][15][16] but the decay of VE against hospitalization had not yet observed as far as we know [14][15][16][17]. In part, this result may be explained by an insufficient time of follow up.…”
Section: Key Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…After completed vaccination schemes, we observed a decay of the VE estimates with time, particularly against symptomatic infection and in the 80 and more yo cohort, where VE decay was observed for both symptomatic infection and hospitalizations. The drop over time of VE against symptomatic infection has also been reported by several authors [14][15][16] but the decay of VE against hospitalization had not yet observed as far as we know [14][15][16][17]. In part, this result may be explained by an insufficient time of follow up.…”
Section: Key Resultsmentioning
confidence: 62%
“…Vaccine effectiveness (VE) against COVID-19 related hospital admissions and mortality in older adults populations varied between 94-97% for the completed vaccination scheme in December 2020 -April 2021 [10][11][12][13]. Following the emergence of the Delta SARS-CoV-2 VOC, studies showed a decrease in VE for both mRNA and AstraZeneca vaccines for symptomatic infections in the general population [14][15][16], but sustained VE estimates against hospitalizations [14][15][16][17] and COVID-19-related mortality [15].…”
Section: Introductionmentioning
confidence: 99%
“…The elderly population is greatly affected by COVID-19, mainly due to the age-related changes affecting immune responses [ 29 ]. Vaccination has been proven essential for the reduction in the severity and mortality of older subjects [ 30 , 31 ], but it is known that age-related immune response defects provoke a lower level of protection after vaccination compared to younger subjects [ 11 , 12 , 13 ]. In this sense, several authors have highlighted the importance of using probiotic supplementation as adjuvants for boosting immunity and enhancing vaccine-specific responses in the elderly population [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, two-dose reg-imen generated high sera-neutralization levels against the Alpha, Beta and Delta variants in individuals sampled at week 8 to week 16 after vaccination [26], being the levels of neutralizing antibodies highly predictive of immune protection from symptomatic SARS-CoV-2 infection [27]. A study at national level estimated high mRNA VE for the prevention of COVID-19-related hospitalizations and deaths (in ≥ 65 years, full vaccinated) with any evidence of VE reduction in the 3 months after the second dose uptake, during the period of Delta variant circulation [28], consistent with the high titers for binding and neutralizing antibodies detected after complete vaccination.…”
Section: Discussionmentioning
confidence: 99%